Evaluación de las características tecnológicas de una arcilla al adicionarle materiales de construcción para fabricar productos estructurales sin ejecutar el proceso de sinterizado (2016)
This research presents a study on the effect of the addition of materials such as sand, cement, and lime on a red clay, with the aim of improving its technological characteristics and avoiding the cooking process. The results of a standard paste were compared with the values thrown in different formulations; the mechanical performance and physical properties of the material are improved, increasing the dry densification and with a decrease in the pressability index. The results showed that adding these materials to produce clay increases the flexural strength between 16,9% and 35,5% and that there is a reduction in dry contraction of around 8,3%, being F7 the formulation that performed the best. These data contribute to the development of ceramic products with added value to be used in various technological applications without sintered material and reducing the energy consumption and pollution that these processes produce.